An Analysis of Poverty in Myanmar, Part 2 : Poverty Profile - Myanmar Ministry of Planning and Finance; World Bank Group (World Bank, Yangon, 2017)
This report presents findings from a joint analysis of poverty and living conditions in 2015, conducted by the Ministry of Planning and Finance and the World Bank Group. The report draws upon the Myanmar Poverty and Living Conditions Survey (MPLCS), fielded in early 2015. Part one of the assessment reviews poverty trends based on previous poverty measurement methodologies used in Myanmar and recommends that the method for measuring poverty is revised to reflect standards of living in 2015. Part two presents the poverty trend and profile based on a new poverty measure.